2012
DOI: 10.1051/0004-6361/201219832
|View full text |Cite
|
Sign up to set email alerts
|

X-shooter spectroscopy of young stellar objects

Abstract: We present high-quality, medium-resolution X-shooter/VLT spectra in the range 300−2500 nm for a sample of 12 very low mass stars in the σ Orionis cluster. The sample includes eight stars with evidence of disks from Spitzer and four without disks, with masses ranging from 0.08 to 0.3 M . The aim of this first paper is to investigate the reliability of the many accretion tracers currently used to measure the mass accretion rate in low-mass young stars and the accuracy of the correlations between these secondary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
293
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(317 citation statements)
references
References 61 publications
23
293
1
Order By: Relevance
“…The calculated accretion rate is consistent with that derived from the empirical relationship between the accretion rate and the H and He emission line luminosities (e.g., Fang et al 2009;Rigliaco et al 2012). The Hα line luminosity yields an accretion rate of (0.3-0.9) × 10 −7 M /yr, while the He 1 λ5875 line luminosity yields (1-2) × 10 −7 M /yr.…”
Section: Analysis: the Structure Of The Accretion Flowsupporting
confidence: 83%
“…The calculated accretion rate is consistent with that derived from the empirical relationship between the accretion rate and the H and He emission line luminosities (e.g., Fang et al 2009;Rigliaco et al 2012). The Hα line luminosity yields an accretion rate of (0.3-0.9) × 10 −7 M /yr, while the He 1 λ5875 line luminosity yields (1-2) × 10 −7 M /yr.…”
Section: Analysis: the Structure Of The Accretion Flowsupporting
confidence: 83%
“…Given that the spectra have very low or zero S/N in the UVB arm, the analysis cannot be performed using the method described in Manara et al (2013b), which simultaneously determines SpT, A V , and accretion luminosity (L acc ), fitting the UV and visible part of the spectra with a grid of models that includes the contribution of photospheric and accretion-induced emission, and reddening. Similarly, the analysis methods used by Alcalá et al (2014) or Rigliaco et al (2012) cannot be adopted here, as all these need to perform a fit of the excess in the UV part of the spectrum to derive L acc , and are well suited for the SpT determination only for objects with low extinction. The procedure we use here is the following: we collect a grid of photospheric templates, which cover the SpT from K5 to L0, with a typical step of 0.5 spectral subclasses throughout the entire M subclass.…”
Section: Methodsmentioning
confidence: 99%
“…These represent the only suitable way to determine L acc from our spectra, as the UV-excess is not detected in the spectra because of the high extinction of the region. This is an indirect method that is less accurate than direct fitting of the UV-excess, but it has been shown that L acc determined in this way are consistent with direct measurements of L acc when multiple lines are used (e.g., Rigliaco et al 2012;Alcalá et al 2014). For this analysis, we then select 11 emission lines that are usually bright and whose L line has a good correlation with L acc , namely CaK, Hδ, Hγ, Hβ, He λ587nm , Hα, He λ667nm , Paδ, Paγ, Paβ, Brγ.…”
Section: Accretion Properties Of ρ-Ophiucus Young Stellar Objectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations for other lines are available in the on-line version of this paper. The line luminosity-accretion luminosity relationship can be approximated by a power law, and has been in numerous works on CTTs and HAeBes (Muzerolle, Hartmann & Calvet 1998;Calvet et al 2004;Dahm 2008;Herczeg & Hillenbrand 2008;Mendigutía et al 2011;Rigliaco et al 2012), where :…”
Section: Accretion Luminosity -Line Luminosity Relationshipsmentioning
confidence: 99%